Managing language learning using Moodle - Abd. Hamid, Mohd Azrul Azlen; Abdullah, Aishah@Adeline Low Hui Lin; Wahab Abdul Rahman, Shahrizal Idzuan; Mat Daud, Nuraihan (IIUM Press, 2012)
This study aims to investigate if the use of MyArabic (using Moodle platform) can help develop students’ writing skills. Students’ perceptions of learning Arabic writing through Moodle were also sought. The study was conducted at a public university in Malaysia on a group of 47 pre-university Arabic language students taking elementary Arabic language course. Data collected using questionnaire survey was analyzed to assess the effectiveness of teaching writing using Moodle platform. The finding of this study suggests that the majority of the students found MyArabic interesting. The study also shows that it can be an effective tool for developing Arabic learners’ writing skills.